Compressors : selection and sizing - Brown, Royce N. (Elsevier, 2005)
This practical reference provides in-depth information required to understand and properly estimate compressor capabilities and to select the proper designs. Engineers and students will gain a thorough understanding of compression principles, equipment, applications, selection, sizing, installation, and maintenance. The many examples clearly illustrate key aspects to help readers understand the "real world" of compressor technology. Compressors: Selection and Sizing, third edition is completely updated with new API standards. Additions requested by readers include a new section on diaphragm compressors in the reciprocating compressors chapter, and a new section on rotor dynamics stability in the chapter on diaphragm compressors. The latest technology is presented in the areas of efficiency, 3-D geometry, electronics, CAD, and the use of plant computers. The critical chapter on negotiating the purchase of a compressor now reflects current industry practices for preparing detailed specifications, bid evaluations, engineering reviews, and installation. A key chapter compares the reliability of various types of compressors. *Everything you need to select the right compressor for your specific application. *Practical information on compression principles, equipment, applications, selection, sizing, installation, and maintenance. *New sections on diaphragm compressors and an introduction to rotor dynamics stability.